2021
DOI: 10.3389/fcell.2021.633937
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial Cancer Associated 1 (UCA1) and miR-193 Are Two Non-coding RNAs Involved in Trophoblast Fusion and Placental Diseases

Abstract: A bioinformatics screen for non-coding genes was performed from microarrays analyzing on the one hand trophoblast fusion in the BeWo cell model, and on the other hand, placental diseases (preeclampsia and Intra-Uterine Growth Restriction). Intersecting the deregulated genes allowed to identify two miRNA (mir193b and miR365a) and one long non-coding RNA (UCA1) that are pivotal for trophoblast fusion, and deregulated in placental diseases. We show that miR-193b is a hub for the down-regulation of 135 cell target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…This function of UCA1 was consistent with that reported in previous studies of UCA1-induced cellular adaptation and survival, including proerythroblast differentiation [ 33 ], adaptation to a toxic environment [ 34 ], and tumor progression [ 35 , 36 ]. Clara Apicella et al [ 37 ] explored the role of UCA1 in activating syncytiotrophoblast, and they also speculated that the upregulation of UCA1 in the preeclamptic placenta might reflect an increase in the turnover of the syncytium to compensate for an increased apoptotic rate. The study by Hongfang Shao et al [ 38 ] also supports the positive regulation of UCA1 in trophoblast invasion, especially in the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…This function of UCA1 was consistent with that reported in previous studies of UCA1-induced cellular adaptation and survival, including proerythroblast differentiation [ 33 ], adaptation to a toxic environment [ 34 ], and tumor progression [ 35 , 36 ]. Clara Apicella et al [ 37 ] explored the role of UCA1 in activating syncytiotrophoblast, and they also speculated that the upregulation of UCA1 in the preeclamptic placenta might reflect an increase in the turnover of the syncytium to compensate for an increased apoptotic rate. The study by Hongfang Shao et al [ 38 ] also supports the positive regulation of UCA1 in trophoblast invasion, especially in the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…In the extravillous pathway, cytotrophoblast cells acquire an invasive phenotype and differentiate into either interstitial extravillous trophoblasts, which invade the decidua and a portion of the myometrium, or endovascular extravillous trophoblasts, which remodel the maternal vasculature [37]. Syncytiotrophoblasts play an important role in maternal-fetal communication [38], but insufficient cell fusion may cause an abnormal syncytiotrophoblast layer and subsequent functional deficits leading to preeclampsia [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…A review by McAninch 12 reported the involvement of lncRNA in various pregnant complications, trophoblast cell function as well as placental immune or inflammatory functions, suggesting the important roles of lncRNA in the development and function of placenta. Among those reported lncRNA in placenta, the human‐specific lncRNA UCA1 that is highly expressed in human trophoblasts attached our attention, and its differential expression has been reported to be linked to different physiopathological statuses of placenta 16 . For instance, the expression of lncRNA UCA1 was upregulated in placentas from patients with preeclampsia (PE) or intrauterine growth restriction (IUGR) or hypoxia conditions, but was decreased in placentas from patients with spontaneous abortion (SA) or recurrent miscarriage 15,16,20–22 .…”
Section: Discussionmentioning
confidence: 99%
“…Among those reported lncRNA in placenta, the human‐specific lncRNA UCA1 that is highly expressed in human trophoblasts attached our attention, and its differential expression has been reported to be linked to different physiopathological statuses of placenta 16 . For instance, the expression of lncRNA UCA1 was upregulated in placentas from patients with preeclampsia (PE) or intrauterine growth restriction (IUGR) or hypoxia conditions, but was decreased in placentas from patients with spontaneous abortion (SA) or recurrent miscarriage 15,16,20–22 . Similarly, differential expression of placental P‐gp has also been widely reported in patients with aforementioned pregnant complications, suggesting a potential regulatory relationship between lncRNA UCA1 and P‐gp in placenta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation